RANCANG BANGUN MESIN PENGUPAS KULIT TELUR PUYUH - Muhammad Akbar; Muhammad Bahit; Rullyansyah; Robert Napitupulu; Muhammad Yunus (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
In the province of the Bangka Belitung islands, many people process quail eggs into various culinary foods. In the process of processing quail eggs must be boiled first until cooked and the peeling process is also still peeled manually or with simple tools, so the peeling process must spend a lot of energy and takes a relatively long time. This study aims to design and manufacture a quail egg shell peeler machine with a 2 screw system mechanism. The research method used is VDI 2222 which stages start with planning, conceptualizing, designing, and completing. The next process is making machine components which are carried out at the Polman Babel workshop then assembling the parts so that they become a machine and then testing and analysis are carried out. Based on the design results, the engine specifications use an electric motor HP 1400 rpm, the transmission system uses a pulley and type A V belt, and the reducer speed is 140 rpm. for the cracking process using a spinner that rotates 70 rpm while the stripping process uses a 2 screw 93 rpm system. Based on the test results obtained on average the machine peeled 16 grains per minute . This quail egg peeler machine has not been able to work optimally because some eggs are crushed and not peeled.